New molecular components of high and low affinity iron import systems in Drosophila - Sattar Soltani; Minyi Yan; Qingxuan Yu; Areeg Abd Elhafiz; Erika Pfriem; Samuel M. Webb; Thomas Kroll; Jahir Marceliano Bahena Lopez; Fanis Missirlis; Kirst King-Jones (Nature Communications)
Abstract The high abundance and molecular versatility of iron have led to its universal presence in biological systems, yet its absorption is exceptionally challenging. Animals and yeasts use divalent metal transporters to import iron, but yeasts also employ the multicopper oxidase Fet3p for high-affinity iron uptake when iron-starved. Using long-term iron depletion in Drosophila, we identified four components involved in iron absorption: Multicopper oxidase-4 (Mco4), a Fet3p ortholog, is essential for surviving iron starvation, whereas the cytochrome b561 enzymes Fire (Ferric Iron Reductase) and Fire-like, as well as cytochrome b5 protein Firewood, are required for iron absorption under normal conditions. This study reports the presence of a high-affinity iron uptake system in an animal, a cytochrome b5 electron donor for ferric iron reduction, and intestinal ferric reductases, and provides a valuable resource for further exploration of genes involved in iron homeostasis, transport, and absorption.